Rethinking Rupture and Continuity: Al-Jarād and Khamāsīn, Two Poetry Magazines of the Egyptian 1990s - Benson, Caroline (AUC Knowledge Fountain, 2025)
This thesis analyzes two Egyptian poetry magazines, al-Jarād and Khamāsīn, to enrich critical understanding of the Egyptian literary 1990s. It uses The Rules of Art: Genesis and Structure of the Literary Field (Les Règles de l’art: Genèse et structure du champ littéraire), Pierre Bourdieu’s 1992 sociological study of the literary field, as a theoretical framework. Numerous scholars have noted that the “nineties generation” is known for its aversion to politics, ideologies, and collectivities; its rupture with stylistic and thematic conventions of its predecessors; and its turn away from the “major issues” (al-qaḍāyah al-kubrā) of the day. I show how contributors to al-Jarād and Khamāsīn sought not a clean break with predecessors but the adoption of a vast multilingual, multimedia, alternative Egyptian cultural heritage whose primary referents were the avant-garde poetry movements of the 1970s and 1980s and the Egyptian surrealist Art and Liberty Collective (Jamāʿat al-Fann wa-l-Ḥurriyyah) (1930s–1940s). Contributors to al-Jarād and Khamāsīn advocated a rupture with dominant political and cultural narratives and an identification with largely marginalized histories of pluralism, rebellion, and dissent; they were guided by the diverse local and a revised cosmopolitan. Combating neoliberalism and establishing an autonomous literary field were the contemporary “major issues” with which these writers were concerned. I argue that rather than taking a direct approach to the neoliberal era by producing literature that reflected deteriorating economic and political realities, the nineties poets staged an inverse response by reifying the poetics of quotidian life and defending art’s autonomy from economic and political institutions.